Саse reроrt оf fetal liver cirrhosis due to gestational alloimmune liver disease in а primigravida femаle, in north east region of India - Gupta, Priya; Maheshwari, Sandip (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Fetal liver failure is a major cause of neonatal morbidity and mortality, presenting as acute liver failure and/or congenital cirrhosis. There are several causes of fetal liver failure and early diagnosis is mandatory to elucidate the etiology and determine a specific treatment or the best management strategy. Gestational alloimmune liver disease associated with neonatal hemochromatosis (GALD-NH) is a rare cause of fetal liver failure. It should be considered in any neonate with fetal signs of liver failure with no other identifiable causes. GALD-NH is often diagnosed late and patients are therefore referred late to specialized centers, delaying treatment. This case highlighted the consequences of late diagnosis and treatment of GALD-NH and emphasizes the importance of a high grade of suspicion of this disease in order to refer the patient to a specialized center soon enough to perform the appropriate treatment.